The Prevalence of Infertility Among Outpatient Department Attendants in Orotta National Referral Maternity Hospital in Asmara-Eritrea, 2007-2015 - Ghirmay Ghebreigziabher (International Journal of Allied Medical Sciences and Clinical Research, 2020)
The clinical definition of infertility is a failure to achieve a clinical pregnancy after 12 months of regular unprotected sexual intercourse. The four main categories of causes of infertility well recognized in clinical practice are male infertility, female infertility, infertility in both male and female partners, and unexplained infertile couples. The objective of the study is to estimate the prevalence and describe the magnitude of identified causes of infertility based on the clinical and laboratory findings of the attendants in Orotta National Referral Maternity Hospital (ONRMH). Methodology A descriptive retrospective cross-sectional study was conducted. The sampling frame and sampling size were based on the patients’ cards of ONRMH. Ethical consideration was thought and permission was obtained from the respected bodies. Results A total of 55287 in reproductive age patients visited the outpatient department (OPD) starting 01/01/ 2007 to 31/12/2015 in ONRMH and 1547 patients were diagnosed as infertility cases. The prevalence of infertility was 2.8%. Majority (82.7%) were couples. About half (43.5%) of the attendants were between 25-34 years old. Almost all of the participants (92.4%) were married. The male factor of infertility was highest 48% followed by female factor 25%. Primary infertility (64%) was more dominant than secondary infertility. Conclusion and Recommendation This study showed that the prevalence of infertility was very low. Male factor and primarily infertility were the highest contributors. Age, sex, and year of visit were found to have significant net effect on infertility. There is a need of public sensitization to increase attendants from all zones to the infertility referral hospital.